Epidemiological surveillance of bovine spongiform encephalopathy in Maranhão: inspection of food provided to ruminants in rural properties (Research, Society and Development, 2022)
The objective of this study was to characterize the epidemiological surveillance system of Bovine Spongiform Encephalopathy (BSE) in the state of Maranhão, from 2016 to 2019. The research was carried out through a descriptive study with a quantitative approach using secondary data from the inspection record rural properties run by the Official Veterinary Service. During the study period, 526 inspections were carried out to monitor food supplied to ruminants in farms, 98.9% of inspections from active surveillance and 1.1% of passive surveillance. Of the 217 municipalities in the state of Maranhão, only 20.3% were inspected, with three cases of animal protein ingestion (poultry litter) were recorded by cattle with laboratory confirmation. Regarding the characterization of the properties, it was observed that 54.8% of the inspections were carried out on properties with beef cattle; 56.7% with extensive breeding system; 60.3% with feeding of ruminants based on pasture associated with concentrates and/or supplements. It was also found that 20% of inspections were carried out on properties with the presence of industrial/commercial poultry farming, 18.3% with poultry litter, and in five properties (1.0%) there was a report of use of poultry litter in ruminant feeding. The results point to the need for continuous surveillance on properties identified as potentially at risk regarding the possible use of animal proteins in the feeding of ruminants in the state of Maranhão, because despite their prohibition, the use of poultry litter to feed the cattle is still practiced.